Faktor-Faktor Yang Mempengaruhi Status Gizi Balita di Wilayah Kerja Puskesmas Prabumulih Timur Tahun 2022 - Afdhal, Fitri; Arsi, Ranida (JURNAL KESEHATAN TERAPAN, 2023)
The nutritional status of children under five can be influenced by various factors including:mother's education level, family income, knowledge, family environment, co-morbidities,consumption of nutrients, parenting style, number of family members, socio-culture. The aim of thestudy was to determine the factors that influence the nutritional status of toddlers in the workingarea of the East Prabumulih Health Center. This type of research is descriptive analytic with crosssectional approach. The number of samples in this study were 91 respondents who were taken byaccidental sampling technique, then interviewed and filled out questionnaires by parents and thenmeasured nutritional status with anthropometry weight/age and compared with the Z-scoreWHO_NCHS. Data analysis was performed with univariate analysis and bivariate analysis. Basedon the results of the study, it was found that variables that were statistically significant related tothe nutritional status of children under five were parents' education (p-value = 0.044), familyincome (p-value = 0.043), parental knowledge (p-value = 0.043) and family environment (p-value= 0.018). Thus it can be concluded that the four factors, namely parents' education, parentalincome, parental knowledge and family environment, have a significant relationship with thenutritional status of toddlers at East Prabumulih Health Center. It is expected that officers willincrease regular monitoring and provide counseling about the nutritional status of toddlers and theimportance of paying attention to toddler health.